1999
DOI: 10.1007/bf01279096
|View full text |Cite
|
Sign up to set email alerts
|

Differential development of plastids during microspore embryogenesis in barley

Abstract: Summary. In order to understand and limit albino plantlet formation during pollen embryogenesis in barley (Hordeum vulgate L. cv. Igri), plastid feature was followed during pollen embryogenesis under two anther culture conditions and compared to plastid development in the zygotic embryo. The first condition was characterized by cold pretreatment and maltose in the induction medium. Both embryos and caUi were then obtained. During pollen embryo development, up to 30% of plastids had abnormal features. Disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…It is possible that direct embryogenesis (without callus phase) of triticale enhances the probability of green plant regeneration. Caredda et al (1999) demonstrated that during direct embryo development up to 30% of the plastids exhibited abnormalities, while among callus-derived embryos up to 50% of the plastids were abnormal, and all regenerants were albino. Harwood et al (1995) reported that of the barley cv.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that direct embryogenesis (without callus phase) of triticale enhances the probability of green plant regeneration. Caredda et al (1999) demonstrated that during direct embryo development up to 30% of the plastids exhibited abnormalities, while among callus-derived embryos up to 50% of the plastids were abnormal, and all regenerants were albino. Harwood et al (1995) reported that of the barley cv.…”
Section: Discussionmentioning
confidence: 99%
“…The research of Caredda and co-workers (1999, 2000, 2004) made a significant contribution to the understanding of plastid physiology in microspores prior to the switch to sporophytic development, at various times during androgenesis itself and in the regenerated plants. Their research focused on two barley cultivars, winter cv.…”
Section: Cytological Studies On Albinismmentioning
confidence: 99%
“…Based on Caredda et al (1999, 2000, 2004), with modifications. Arrows indicate the trend relative to the previous column…”
Section: Cytological Studies On Albinismmentioning
confidence: 99%
See 1 more Smart Citation
“…High frequency of albino plant formation in anther and microspore cultures is a general phenomenon in most cereals like wheat (Andersen et al 1987), barley (Knudsen et al 1989, rice , rye (Immonen 1999), oat and in several grasses like ryegrass (Olesen et al 1988) and timothe (Abdullah et al 1994). These white plants contain plastids arrested in development towards functional chloroplasts (Caredda et al 1999Sun et al 1974) and therefore cannot grow without the sugar containing media of in vitro cultures (Sun et al 1974). …”
Section: Introductionmentioning
confidence: 99%